Succulent Plant Management Information System for Nursery Gardening Store - Teoh, Shieh Zheng; Binti Arbaiy, Nureize (Applied Information Technology And Computer Science, 2023)
Succulents can be seen for sale in most plant nurseries. The nursery aims to produce high quality succulents for the satisfaction of its customers. However, the quality of the succulent will deteriorate easily through some mistakes of its care. This includes watering schedules and other maintenance that must be planned of time. The schedule of tasks in the nursery for watering and planting should be implemented accordingly to ensure that the succulents are healthy and become an inventory ready for sale later. This challenge proposes that a management information system for succulent nurseries is needed to improve task execution efficiency by scheduling, tracking succulent state, and providing reports. Therefore, a succulent nursery store management information system has been developed to address the issues in discussion. A prototype model has been implemented. The functional modules in this system consist of login and registration module, task management module, succulents planting management module, succulent inventory module, and report generation module. Program code is written using PHP, Sublime Text, and Macromedia Dreamweaver 2021 and MySQL and XAMPP are used to administer the database. The system has been developed and is able to perform as intended. The system provides a web-based platform for easier management of succulents and chores, improved security for nursery data, and a database for storing important data to its customers.